Pengaruh Pengaruh Perilaku Kewirausahaan Terhadap Kinerja Usaha Kecil (Pada Usaha Jagung Rebus di Kabupaten Takalar) - Riska Nur Apriyanti; Muhammad Rakib; Agus Syam; Marhawati Marhawati Marhawati; Muh Ihsan Said (Economic Education and Entrepreneurship Journal, 2021)
The purpose of this finding is to determine the impact of entrepreneurial behavior on the performance of small businesses (on corn on the cob in Takalar Regency). This research is quantitative. Simple regression analysis was used to evaluate hypotheses, while data collection was carried out by distributing questionnaires to business people. entrepreneurship is an important factor in improving the performance of small businesses.Keywords: Entrepreneurial Behavior, Business Performance